Regulation of the ErbB network by the MIG6 feedback loop in physiology, tumor suppression and responses to oncogene-targeted therapeutics. (February 2016) - Anastasi, Sergio; Lamberti, Dante; Alemà, Stefano; Segatto, Oreste
Highlights: MIG6 plays a necessary role of in negative feedback regulation of ErbB receptors. MIG6 suppresses EGFR signaling via kinase inhibition and down-regulation. MIG6 loss enhances oncogenic ErbB signaling. MIG6 loss in tumors is a potential biomarker of oncogenic addiction to ErbB signaling. Abstract: The ErbB signaling network instructs the execution of key cellular programs, such as cell survival, proliferation and motility, through the generation of robust signals of defined strength and duration. In contrast, unabated ErbB signaling disrupts tissue homeostasis and leads to cell transformation. Cells oppose the threat inherent in excessive ErbB activity through several mechanisms of negative feedback regulation. Inducible feedback inhibitors (IFIs) are expressed in the context of transcriptional responses triggered by ErbB signaling, thus being uniquely suited to regulate ErbB activity during the execution of complex cellular programs. This review focuses on MIG6, an IFI that restrains ErbB signaling by mediating ErbB kinase suppression and receptor down-regulation. We will review key issues in MIG6 function, regulation and tumor suppressor activity. Subsequently, the role for MIG6 loss in the pathogenesis of tumors driven by ErbB oncogenes as well as in the generation of cellular addiction to ErbB signaling will be discussed. We will conclude by analyzing feedback inhibition by MIG6 in the context of therapies directed against ErbB and non-ErbB oncogenes.